2012
DOI: 10.3389/fpsyg.2012.00187
|View full text |Cite
|
Sign up to set email alerts
|

Integration or Predictability? A Further Specification of the Functional Role of Gamma Oscillations in Language Comprehension

Abstract: Gamma-band neuronal synchronization during sentence-level language comprehension has previously been linked with semantic unification. Here, we attempt to further narrow down the functional significance of gamma during language comprehension, by distinguishing between two aspects of semantic unification: successful integration of word meaning into the sentence context, and prediction of upcoming words. We computed event-related potentials (ERPs) and frequency band-specific electroencephalographic (EEG) power c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
118
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(137 citation statements)
references
References 35 publications
16
118
3
Order By: Relevance
“…power increase in the lower Gamma (35-45Hz) has been associated with the processing of correct sentences compared to sentences containing semantic violations (Hald et al, 2006;Wang et al, 2012; but see the increase in gamma for world knowledge violations observed in Hagoort et al, 2004); also the power increase in middle gamma range (50-70Hz) has been reported for successful sentence processing (Penolazzi et al, 2009;Monsalve, Perez & Molinaro, 2014). Despite the different frequency ranges of lower and middle gamma bands, and the different time development of the effects observed (sustained in time, Hald et al, 2006;Penolazzi et al, 2009;Wang et al, 2012;or short lasting, Monsalve et al, 2014), according to a recent interpretation of these changes the increase in gamma power would reflect reverberatory activity triggered by a successful match "between the pre-activation of the neural representation of the predicted word, and the neural representation of the actually incoming word" (Wang et al,p.11).…”
Section: Gamma Band Frequency and Semantic Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…power increase in the lower Gamma (35-45Hz) has been associated with the processing of correct sentences compared to sentences containing semantic violations (Hald et al, 2006;Wang et al, 2012; but see the increase in gamma for world knowledge violations observed in Hagoort et al, 2004); also the power increase in middle gamma range (50-70Hz) has been reported for successful sentence processing (Penolazzi et al, 2009;Monsalve, Perez & Molinaro, 2014). Despite the different frequency ranges of lower and middle gamma bands, and the different time development of the effects observed (sustained in time, Hald et al, 2006;Penolazzi et al, 2009;Wang et al, 2012;or short lasting, Monsalve et al, 2014), according to a recent interpretation of these changes the increase in gamma power would reflect reverberatory activity triggered by a successful match "between the pre-activation of the neural representation of the predicted word, and the neural representation of the actually incoming word" (Wang et al,p.11).…”
Section: Gamma Band Frequency and Semantic Compositionmentioning
confidence: 99%
“…Despite the different frequency ranges of lower and middle gamma bands, and the different time development of the effects observed (sustained in time, Hald et al, 2006;Penolazzi et al, 2009;Wang et al, 2012;or short lasting, Monsalve et al, 2014), according to a recent interpretation of these changes the increase in gamma power would reflect reverberatory activity triggered by a successful match "between the pre-activation of the neural representation of the predicted word, and the neural representation of the actually incoming word" (Wang et al,p.11). This explanation (see also Lewis & Bastiaansen, 2015) processes involved in processing highly predictable strings.…”
Section: Gamma Band Frequency and Semantic Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothalamic abnormalities in schizophrenia were associated with endocrine dysfunction the stress response and the hypothalamic-pituitary-adrenal (HPA) axis [54]. Patients with schizophrenia spectrum had a larger pituitary volume (larger in female than male patients), reflecting hyperactivity of the HPA axis, which may be related to a common vulnerability to stress in patients [63].…”
Section: Hypothalamusmentioning
confidence: 99%
“…Gamma ERS has been implicated in the coordination of activity between distributed neuronal assemblies in the service of sensory registration of stimuli and perceptual binding of their features, and schizophrenia patients have demonstrated deficits in the magnitude and/or phase synchrony of stimulus-evoked gamma oscillations [53]. Gamma ERS during sentence-level language comprehension has previously been linked with semantic unification, and increased gamma power was related to the predictability of an upcoming word based on the preceding sentence context [54]. Gamma ERS was associated with cortical activation while imagining the movement of body parts, and appeared to be located near somatosensory and motor areas [55].…”
Section: Precuneusmentioning
confidence: 99%